2003
DOI: 10.1210/jc.2002-020867
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Response to Growth Hormone Treatment in Short Children Born Small for Gestational Age: Analysis of Data from KIGS (Pharmacia International Growth Database)

Abstract: A model was developed that allows physicians to individualize GH treatment in children born short for gestational age (SGA) who fail to show spontaneous catch-up growth. Data from children (n = 613) in a large pharmacoepidemiological survey, the KIGS (Pharmacia International Growth Database), or who had participated in clinical trials were used to develop the model. Another group of similar children (n = 68) from KIGS was used for validation. In the first year of GH treatment, the growth response correlated po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
162
2
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(180 citation statements)
references
References 20 publications
6
162
2
10
Order By: Relevance
“…A idade óssea no início do tratamento, em acordo com a literatura (7,20), foi identificada como uma das variáveis preditoras do ganho estatural no primeiro ano de tratamento, ressaltando a correlação negativa com o ganho estatural (21).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A idade óssea no início do tratamento, em acordo com a literatura (7,20), foi identificada como uma das variáveis preditoras do ganho estatural no primeiro ano de tratamento, ressaltando a correlação negativa com o ganho estatural (21).…”
Section: Resultsunclassified
“…Apesar de alguns estudos demonstrarem relação direta entre dose e resposta ao tratamento nas crianças nascidas PIG (7,8,14,15), nosso estudo mostrou que a dose fixa de 1,0 UI/kg/semana (0,33 mg/kg/semana) foi capaz de promover um catch up de crescimento rele-Arq Bras Endocrinol Metab. 2010;54/5…”
Section: Discussionunclassified
See 1 more Smart Citation
“…on the ISS curve according to gender (20) or height velocity between 7 and 11.4 cm (10th-90th percentiles) for SGA children (21)); and ii) good height response (defined as height gain O0.5 S.D.) (22); plus iii) (if available) normalization of IGF1 levels to the normal range for chronological age and pubertal stage.…”
Section: Methodsmentioning
confidence: 99%
“…The International Societies of Pediatric Endocrinology and the Growth Hormone Research Society consensus statement proposes that children born SGA with height below −2.5 SDs at age 2, or with height below −2 SDs at age 4, should be treated with growth hormone (5). It is well known that one of the major factors for a good response to growth hormone therapy is lower age, so it is suggested that all short SGA children older than four years are candidates for growth hormone therapy (6,10).…”
Section: Introductionmentioning
confidence: 99%